Pengaruh Persepsi Harga Dan Promosi Penjualan Terhadap Minat Beli Konsumen Restoran - Rafli Kurniawan; Gen Gen Gendalasari (Jurnal Ilmiah Pariwisata Kesatuan, 2021)
The purpose of this research was to determine the factors of Price Perception and Sales Promotion which can affect buying interest in A&W Fast Food Restaurant products. This research use independent variable (Price Perception and Sales Promotion) and dependent variable (Purchase Interest). This research was conducted in Bogor, with the data collection method using a questionnaire distributed to 100 respondents. The research data was processed using the SPSS program. The results of this study are (1) Price Perception has a positive and significant effect on Purchase Interest on A&W Fast Food Restaurant products with a regression coefficient value of 0.545 and a significance value of 0.000. (2) Sales Promotion has a positive and significant effect on Buying Interest on A&W Fast Food Restaurant products with a regression coefficient value of 0.296 and a significant value of 0.002. (3) Price Perception and Sales Promotion have a positive and significant effect on Buying Interest in A&W Fast Food Restaurant products with a calculated F value of 52.162 and greater than F table 2.46 with a significance value of 0.000. Keywords: Price Perception, Sales Promotion and Purchase Interest.